2022
DOI: 10.1177/1071181322661439
|View full text |Cite
|
Sign up to set email alerts
|

Critical Decision Method Interviews to Understand the Initial Treatment Planning Process in Foster Care

Abstract: In foster care settings, the treatment plan captures goals and interventions for youth in care. The first version of this plan is typically due 30 days after the youth is enrolled in the foster care program, leading to a challenging month of assessing the case and developing the treatment plan. This study utilized Critical Decision Method interviews with care coordinators and clinicians to understand the decision-making involved in balancing assessment tasks, and the barriers to using assessment to inform trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…We developed this abstraction hierarchy of Hillside’s therapeutic foster care program using our understanding of the domain that stemmed from a range of data sources. A previous interview study conducted with five care coordinators and clinicians at Hillside provided many useful insights about the first 30 days of the therapeutic foster care treatment planning process (Wurst et al, 2022). This study utilized the Critical Decision Method (Klein et al, 1989) to review particularly challenging instances of treatment planning resulting in a better understanding of process, constraints, and the general workplace ecology.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We developed this abstraction hierarchy of Hillside’s therapeutic foster care program using our understanding of the domain that stemmed from a range of data sources. A previous interview study conducted with five care coordinators and clinicians at Hillside provided many useful insights about the first 30 days of the therapeutic foster care treatment planning process (Wurst et al, 2022). This study utilized the Critical Decision Method (Klein et al, 1989) to review particularly challenging instances of treatment planning resulting in a better understanding of process, constraints, and the general workplace ecology.…”
Section: Methodsmentioning
confidence: 99%
“…These criticisms are not meant to imply that technological solutions are unnecessary, as practitioner-driven decision-making also has some limitations. Practitioners are often overloaded with information of uncertain accuracy from a variety of sources (Wurst et al, 2022), which can lead to a lack of adherence to assessment protocol. For example, a think-aloud study examining foster family matchmaking found that analytical guidelines were underused in decision-making and that practitioners instead relied on heuristics to offset time and resource constraints (Zeijlmans et al, 2019).…”
Section: Background Foster Care -Domain Perspectives and Constraintsmentioning
confidence: 99%
See 3 more Smart Citations